2015
DOI: 10.1002/ange.201410632
|View full text |Cite
|
Sign up to set email alerts
|

Der elektronische Faktor in der Alkanoxidationskatalyse

Abstract: Die vorliegende Arbeit beschäftigt sich mit der fundamentalen Frage, inwieweit halbleiterphysikalische Konzepte nützlich sind, um die Arbeitsweise heterogener Oxidationskatalysatoren zu beschreiben und ob es mithilfe dieser Konzepte sogar möglich ist, zwischen selektiven und unselektiven Reaktionspfaden zu differenzieren. Mit In-situ-Röntgenphotoelektronenspektroskopie konnte am Beispiel der Oxidation von n-Butan zu Maleinsäureanhydrid über dem hochselektiven Katalysator Vanadylpyrophosphat und der mäßig selek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…[27][28][29] In the homolytic activation mechanism, the C−H bond is activated by charge transfer between methane and catalyst surface to form the alkyl radical and a formally H radical. 25,26,30 For the iron-based catalyst, it has been reported that heterolytic C−H dissociation is commonly observed over low-valence Fe sites (e.g., 2+) conjugated with a strong basic site, while the homolytic C−H cleavage occurs on high-valence Fe sites. 25 Besides these two generic reaction mechanisms, a Fenton-type mechanism of C−H activation has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] In the homolytic activation mechanism, the C−H bond is activated by charge transfer between methane and catalyst surface to form the alkyl radical and a formally H radical. 25,26,30 For the iron-based catalyst, it has been reported that heterolytic C−H dissociation is commonly observed over low-valence Fe sites (e.g., 2+) conjugated with a strong basic site, while the homolytic C−H cleavage occurs on high-valence Fe sites. 25 Besides these two generic reaction mechanisms, a Fenton-type mechanism of C−H activation has also been reported.…”
Section: Introductionmentioning
confidence: 99%